2019
DOI: 10.1136/bmjgast-2019-000315
|View full text |Cite
|
Sign up to set email alerts
|

High potency multistrain probiotic improves liver histology in non-alcoholic fatty liver disease (NAFLD): a randomised, double-blind, proof of concept study

Abstract: ObjectivePharmacological treatment of non-alcoholic fatty liver disease (NAFLD) is still evolving. Probiotics could be a promising treatment option, but their effectiveness needs to be established. The present study aimed to evaluate the efficacy of a high potency multistrain probiotic in adult patients with NAFLD.MethodsThirty-nine liver biopsy-proven patients with NAFLD were randomised in a double-blind fashion to either lifestyle modifications plus an oral multistrain probiotic (675 billion bacteria daily, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(113 citation statements)
references
References 39 publications
4
104
0
5
Order By: Relevance
“…Small scale studies with probiotics conducted in patients with NAFLD and alcohol-related liver disease in pre-cirrhotic phases yielded only mixed results and are not translatable into clinical practice. 95,96 Major improvement in outcomes pertaining to the use of obeticholic acid in PBC could be partly related to microbial modulation. 97 Preliminary studies using vancomycin in PSC have shown promise in the pre-cirrhotic stage.…”
Section: Key Pointmentioning
confidence: 99%
“…Small scale studies with probiotics conducted in patients with NAFLD and alcohol-related liver disease in pre-cirrhotic phases yielded only mixed results and are not translatable into clinical practice. 95,96 Major improvement in outcomes pertaining to the use of obeticholic acid in PBC could be partly related to microbial modulation. 97 Preliminary studies using vancomycin in PSC have shown promise in the pre-cirrhotic stage.…”
Section: Key Pointmentioning
confidence: 99%
“…LGG High-fructose diet-fed mice ↑ Gut beneficial bacteria ↑ TJ-related protein expression ↓ Lipid accumulation ↓ ALT level [ 127] HFD-fed mice ↓ Fat content ↓ Serum TAG and cholesterol levels ↓ Liver inflammation [ 128] Bifidobacterium HFD-fed NAFLD rats ↓ Liver fat accumulation [ 129] NAFLD subjects ↓ Body weight and BMI ↓ TNF-level ↑ Serum antioxidant capacity [ 166] (Continued) HFD-fed mice ↓ Hepatic NKT cell depletion ↓ IR and hepatic steatosis [ 132] MCD-fed NASH mice ↓ Liver fibrosis [ 133] Lactococcus lactis subsp. cremoris Western diet-fed female mice ↓ Hepatic steatosis ↓ Liver fat inflammation ↓ IR and serum cholesterol level [ 134] Multistrain probiotic NAFLD patients ↓ NAS score ↓ Hepatic fibrosis ↓ Hepatocyte ballooning ↓ ALT and TNF-levels [ 135] Prebiotics Inulin-type fructans ApoE −/− mice fed a N-3 PUFA-depleted diet ↓ Hepatic inflammation ↑ GLP-1 and BA turnover [ 137] NASH patients ↓ ALT and AST levels [ 138] FOS MCD-fed NASH mice ↓ Hepatic steatosis ↓ Liver inflammation ↑ Gut barrier strength [ 140] IMOs HFD-fed NAFLD mice ↓ Weight gain ↓ IR and adiposity [ 141] Symbiotics Bifidobacterium longum with FOS NASH patients ↓ TNF-and serum LPS ↓ Hepatic steatosis ↓ NASH activity index [ 143] Seven probiotics and FOS NAFLD patients ↓ Hepatic steatosis ↓ Liver fibrosis ↓ ALT and AST levels [ 144] LBSF containing L. casei, L. rhamnosus, L. bulgari, B. longum, S. thermophilus, and FOS NASH patients ↓ ALT level ↓ Liver stiffness ↓ BMI and serum cholesterol [ 145] Lactobacillus reuteri with guar gum and inulin NASH patients ↓ Hepatic steatosis ↓ Weight gain [ 146] Arrows indicate an increase (↑) or decrease (↓) in the level of gene expression, protein activity, or phenotypic change. QHD, Qushi Huayu decoction; GC, geniposide and chlorogenic acid; DCHD, dachaihu decoction; WEGL, a water extract of Ganoderma lucidum mycelium; WD/VDD +/+ diet, westernized diet (high-fat/high-fructose corn syrup) deficient in vitamin D;…”
Section: Mastihamentioning
confidence: 99%
“…[134] In addition, one randomized trial demonstrated that multi-strain probiotic (lactic acid bacteria and bifidobacteria) with exercise interventions can effectively alleviate NAFLD-related pathological phenotypes in biopsy-proven NAFLD patients. [135] Of note, apart from the benefits for liver diseases, our team recently investigated the role of two major probiotics (Lactobacillus casei LC122 and Bifidobacterium longum BL986) in anti-aging via regulation of the gut microbiota. [136] A prebiotic is a substrate selectively utilized by the host microbiome that is beneficial for host health.…”
Section: Probiotics Prebiotics and Symbioticsmentioning
confidence: 99%
“…Choline plays critical role in the process of very-low-density lipoprotein VLDL synthesis and facilitates hepatic lipid exportation. Thus choline deficiency results in triglyceride accumulation in hepatocytes [69]. A small human case study indicated that long-term total parenteral nutrition (TPN) without choline supplementation induced hepatic steatosis.…”
Section: Pathogenesis: the Links Between Nafld And Microbiomementioning
confidence: 99%